Problem Based Learning Increases Fifth Grade Social Sensitivity: Pembelajaran Berbasis Masalah Meningkatkan Kepekaan Sosial Siswa Kelas Lima - Rahayu, Christianti Ellis; Rezania, Vanda (Indonesian Journal of Education Methods Development, 2026)
General Background: Character education in the Society 5.0 era requires the strengthening of social sensitivity to support harmonious social interaction among elementary students. Specific Background: Observations in Grade 5 Nyai Walidah at SD Plus Muhammadiyah Brawijaya indicated low levels of social sensitivity, reflected in limited cooperation, low empathy, weak emotional regulation, and minimal classroom interaction. Knowledge Gap: Although previous studies have applied Problem Based Learning in social studies contexts, limited classroom action research has specifically examined its structured implementation to address four aspects of social sensitivity: perspective-taking, empathy, emotional regulation, and theory of mind in primary education. Aims: This study aims to increase students’ social sensitivity through the implementation of the Problem Based Learning model in IPAS learning. Results: Using a Classroom Action Research design with two cycles, findings show an increase in social sensitivity levels from 66.8% in Cycle I to 96.5% in Cycle II, supported by observable improvements in cooperation, respect, emotional control, and responsiveness during group discussions. Novelty: The study integrates contextual social issues and structured monitoring outside the research cycle within the PBL framework to strengthen measurable social sensitivity indicators. Implications: The findings provide pedagogical guidance for elementary teachers in designing collaborative, problem-oriented IPAS instruction to foster social character development. Keywords: Social Sensitivity, Problem Based Learning, Character Education, Classroom Action Research, Elementary Students Key Findings Highlights Social awareness scores rose from 66.8% to 96.5% across cycles Stronger peer interaction observed during collaborative tasks Emotional control and empathy demonstrated in group discussions